Age-related changes of elements in the coronary arteries of monkeys in comparison with those of humans - Tohno Y. (2014)
To elucidate compositional changes of the coronary artery with aging, the authors investigated age-related changes of elements in the coronary arteries of rhesus and Japanese monkeys by direct chemical analysis in comparison with the coronary arteries of Japanese and Thai. Used monkeys consisted of 38 rhesus monkeys and 23 Japanese monkeys, ranging in age from newborn to 33 years. After perfusion with a fixative, the hearts were resected from the monkeys, and the anterior interventricular branches of the left coronary artery and the right coronary arteries were resected from the hearts. After ashing of the arteries, element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that the Ca and P contents did not increase in both the left and right coronary arteries of rhesus and Japanese monkeys at old age. The average contents of Ca and P decreased by 13% and 25% in the left coronary arteries more than 20 years of age in comparison with those below 20 years of age, whereas they decreased by 4% and 15% in the right coronary arteries more than 20 years of age in comparison with those below 20 years of age. This finding indicated that atherosclerosis scarcely occurred in both the left and right coronary arteries of rhesus and Japanese monkeys at old age. In contrast with monkeys, atherosclerosis occurred frequently in the coronary arteries of Japanese and Thai at old age. © 2008 Humana Press Inc.